Factors Associated with Women's Unwillingness to Decrease Alcohol Intake to Decrease Breast Cancer Risk - Jenna Matin; Rachel McFarland Lucia; Krustina Lal; Alyssa Columbus; Deborah Goodman; Kathryn Larsen; Argyrios Ziogas; Hannah Lui Park (SAGE Publishing, 2021)
Objective: Alcohol intake is a known risk factor for breast cancer. National organizations recommend that women consume no more than one serving of alcohol per day, if at all; however, many women exceed this recommendation, and some are unwilling to decrease consumption. Our study sought to identify factors associated with women's unwillingness to decrease their alcohol intake to decrease their breast cancer risk. Methods: 942 women in a screening mammography cohort were asked questions about their demographics, personal and family health history, lifestyle factors, and willingness/unwillingness to decrease alcohol intake to decrease their breast cancer risk. Univariate and multivariate analyzes of their responses were performed. Results: 13.2% of women in our cohort indicated they were unwilling to decrease their alcohol intake to reduce their breast cancer risk. After adjusting for potential confounders, women who were 60 years and older were more than twice as unwilling to decrease their alcohol intake compared to their younger counterparts ( P  = .0002). Women who had an annual household income of more than $200,000 were 1.75 times more unwilling to decrease their alcohol intake compared to their less affluent counterparts ( P  = .033). Unwillingness was not significantly associated with race/ethnicity, education, having a first-degree family member with cancer, health perception, breast cancer risk perception, or BMI. Conclusions: Levels of unwillingness to decrease alcohol intake differed by age and household income. An opportunity is present to potentially decrease breast cancer risk in the community by educating women, especially older and more affluent women, about alcohol as a risk factor for breast cancer and the importance of limiting one's alcohol intake.